CARTOGRAPHIC IMAGE OF THE STRAIT OF MAGELLAN DURING THE FIRST TWO DECADES FOLLOWING ITS DISCOVERY LA IMAGEN CARTOGRÁFICA DEL ESTRECHO DE MAGALLANES EN LAS DOS PRIMERAS DÉCADAS QUE SIGUIERON A SU DESCUBRIMIENTO - MATEO MARTINIC, B. (My University, 2020)
The discovery and navigation of the interoceanic passage through the New World by Fernando de Magallanes in 1520, once it was known by the Spanish authorities after the return of the nao Victoria in September 1522, was valued as a geographical fact of the greatest importance for the Castilian crown. Consequently, and on the basis of the precarious information provided by the survivors of the historical world tour, it was able to be placed immediately on the maps that provided a new and enlarged image of the planet as it was being known. This article considers the stages and forms of a cartographic evolution from the simple initial sketch to the most elaborated particular expression of the early famous channel, obtained after two decades of patient news gathering about it, and of an increasingly careful and reliable professional task.
Keywords: cartography; patagonia; strait of magellan; tierra del fuego